2020
DOI: 10.1017/s1355617720000661
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Plasticity Under Adverse Listening Conditions is Disrupted in Developmental Dyslexia

Abstract: Objective: Acoustic distortions to the speech signal impair spoken language recognition, but healthy listeners exhibit adaptive plasticity consistent with rapid adjustments in how the distorted speech input maps to speech representations, perhaps through engagement of supervised error-driven learning. This puts adaptive plasticity in speech perception in an interesting position with regard to developmental dyslexia inasmuch as dyslexia impacts speech processing and may involve dysfunction in neurobiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 96 publications
(158 reference statements)
1
13
0
Order By: Relevance
“…We argue that people with DD are less able to use sensory low-level information efficiently, which leads to greater reliance on top-down information as a compensatory mechanism. This notion is consistent with previous findings in which the ability of dyslexics to generalize speech perceptual learning was intact when trained and untrained information shared high-level top-down information (Gabay et al, 2017) but not when shared information was based only on low-level sub-lexical cues (Gabay et al, 2017;Gabay & Holt, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We argue that people with DD are less able to use sensory low-level information efficiently, which leads to greater reliance on top-down information as a compensatory mechanism. This notion is consistent with previous findings in which the ability of dyslexics to generalize speech perceptual learning was intact when trained and untrained information shared high-level top-down information (Gabay et al, 2017) but not when shared information was based only on low-level sub-lexical cues (Gabay et al, 2017;Gabay & Holt, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…In typical listeners, the learning of distorted speech generalizes across stimuli that share high-level representations (new talker, same tokens) but also to new items that do not share high-level representations with the trained one (same talker, new tokens) (Banai & Lavner, 2012Gabay et al, 2017). By contrast, for individuals with DD, such generalization is confined to situations in which trained and untrained information shares the same high-level top-down information (new talker, same tokens) (Gabay et al, 2017) but is not observed in situations in which only low-level sub-lexical cues are shared between the trained and untrained information (same talker, new tokens) (Gabay et al, 2017;Gabay & Holt, 2021). Therefore, it seems that people with DD are capable of adapting to acoustic challenges when utilization of top-down information is possible.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is possible that individuals with dyslexia have a reduced capacity for rapidly adapting to speech cues in order to identify and discriminate between phonemes, resulting in underspecified phonological representations. Indeed, there is evidence for both general auditory and speech-specific adaptation deficits in individuals with dyslexia (Ahissar Amitay et al, 2002;Gabay et al, , 2019, 2021Perrachione et al, 2016).…”
Section: Speech-specific Perceptual Adaptation Deficits In Children and Adults With Dyslexiamentioning
confidence: 99%
“…The challenges to developing fluent reading skills in dyslexia must therefore come from latent dysfunction in either the circuits that develop into the reading network or the plasticity processes that support repurposing those circuits for reading. In this study, we investigated the neural bases of differences in rapid perceptual adaptation in dyslexia—a recently documented, domain-general deficit that may reflect weakness in the plasticity processes that support learning to read (Ahissar et al, 2006; Gabay & Holt, 2020; Jaffe-Dax et al, 2016; Oganian & Ahissar, 2012). Specifically, we aimed to expand on the evidence for diminished neural adaptation in dyslexia (Perrachione et al, 2016) by determining whether this phenomenon is due to differences in bottom-up feedforward processing, top-down expectations, or their interaction.…”
Section: Introductionmentioning
confidence: 99%